Erythrina velutina WILLD. E Schinus terebinthifolia RADDI em áreas de reflorestamento e remanescentes de Mata Atlântica e Caatinga - Souza, Erica Moraes Santos de (2018)
The aspects related to the genetic diversity of forest species have been discussed in recent forest restoration projects. These aspects have needed to be seriously considered for the formation of new forests and in order to improve the older restoration areas. The use of tools, such as molecular markers (ISSR and SSR) and species distribution modeling (MDE), provide important information for collecting plant materials. Both of these are useful tools for indicating areas for planting and for biodiversity conservation, as well as being a guide in the elaboration of forest management plans. Erythrina velutina Willd. (Fabaceae-Papilionoideae) and Schinus terebinthifolia Raddi (Anacardiaceae) are two species that stand out the most in present forest restoration projects in the State of Sergipe, Brazil, due to their fast growth, their rusticity and their plasticity. However, little is known about their genetic diversity in reforestation areas. Therefore, the objectives of this study were: i) to estimate and to compare the genetic diversity of E. velutina and S. terebinthifolia in an area of mixed reforestation, after 12 years of planting and in the native forest remnants in the State of Sergipe; ii) to evaluate the genetic selfsustainability capacities for those populations in the reforested area; and iii) to subsidize strategies for their conservation and their seed collection in future restoration projects. The individuals of E. velutina and S. terebinthifolia that were sampled from the reforested area presented high rates of genetic diversity, when in relation to the natural remnants. This indicated that the area was established with a high genetic diversity of the seedlings. The E. velutina population that was located in the reforestation area, together with the Carmópolis/Rosário do Catete and the Laranjeiras natural populations, showed a significant number of loci with an excess of heterozygosity, inferring the existence of a recent genetic bottleneck. The MDE analyzes indicated that until the year 2050, there would be an expansion of areas with a high environmental suitability for the development of E. velutina, which would contribute to the species conservation plans. However, the human factor is always the variable with the greatest of impacts for this occurrence. For the S. terebinthifolia, there were found higher coefficients of endogamy and coancestry within the reforested population. A reduction of genetic diversity in the juveniles was also observed. The effective population size in both of the populations (reforested and natural) was lower than that recommended for the conservation of populations in the short and long terms. The future seed collections of E. velutina and S. terebinthifolia can be carried out in the natural remnants being studied, provided that they respect the established criteria, such as a minimum distance between the individuals, whilst avoiding isolated trees and their related individuals. The studied results have supported the fact that it is necessary for the application of techniques that promote a connectivity among the fragments, allowing for a reduction of the effects of genetic drift and the persistence of the reforested population.